Increasing Community Knowledge Regarding Hypertension in Kanreapia Village, Gowa Regency - Sadarang, Rimawati Aulia Insani; Rusmin, Muhammad; Hajra, Andi; Ahadits, Mukhtarul; Ramadani, Putri; Putri, Leoni Amanda (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2024)
Hypertension is a major health problem that can affect people in developing countries, especially rural communities. This disease can result in health problems in the body's internal organs such as the heart, brain and kidneys. This activity aims to increase public knowledge regarding hypertension and implement preventive methods to prevent hypertension. Counseling regarding hypertension was carried out using the lecture method in Balanlohe Hamlet, Kanreapia Village, Kuncio Pao District, Gowa Regency. By displaying a PPT (Power Point) which contains material about hypertension. Pre and post tests were given to determine changes in knowledge before and after the counseling was given. Shows that based on the difference in pre-test and post-test results, there was an increase in knowledge from 6.7% who had good knowledge before counseling to 80% after being given counseling. Based on the results of the Paired Samples T Test, it shows that there is a significant difference in knowledge both before and after hypertension education. The results of this activity recommend that people adopt a healthy lifestyle, use iodized salt, exercise regularly, and have regular health checks at the nearest health facility.